A conceptual model of corporate storytelling for branding - Brighton Nyagadza; Ernest Kadembo; Africa Makasi (Communicare)
The purpose of this conceptual paper is to ascertain the relationship between corporate storytelling for branding and internal stakeholders’ perceptions of the corporate brand. The paucity of existing knowledge found in reviewing a variety of literature sources relating to corporate brand storytelling spurred the authors into carry out the research. The link between themes and elements of corporate stories for branding and strategies for impression management indicates that these elements relate to audiences’ perceptions of the corporate brand. From the literature review, there is a link between elements of corporate stories for branding (such as corporate personalities, corporate activities, corporate values, and corporate associations) and internal stakeholders’ perceptions and emotional attachment to a corporate brand. Corporate management needs to actively involve internal stakeholders in developing corporate stories for branding as this is crucial in creating positive corporate brand perceptions. The study contributes to the body of knowledge by allowing listed corporates to maximise the effectiveness of their corporate stories for branding in shaping the internal stakeholders’ corporate brand perceptions. The paper suggests a conceptual model for depicting the relationship between corporate storytelling for branding and internal stakeholders’ corporate brand perceptions.